Technology blueprint of Smart Tech Wash / Nur Syafizah Mohd Aliman, Nini Syafini Zaidi and Marhain Hanani Husin - MOHD ALIMAN, NUR SYAFIZAH; ZAIDI, NINI SYAFINI; HUSIN, MARHAIN HANANI (2018)
After initial observation towards the self - service laundry, the team had chosen a product that we believe can contribute to the community. The product is Smart Tech Wash (STW). Nowadays, commercial washing machine user tend to leave their laundry for longer time because there is no reminder and causing others to wait for their turn. Some customer does not prefer to unload others' clothes because there is no permission given. Thus, the team generate the ideas for the commercial washing machine to be connected to an apps and provide permission messages.